1997
DOI: 10.1016/s0014-5793(97)00481-x
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal nitric oxide synthase PDZ motif binds to ‐G(D,E)XV* carboxyterminal sequences

Abstract: PDZ motifs are small protein-protein interaction modules that are thought to play a role in the clustering of submembranous signalling molecules. The specificity and functional consequences of their associative actions is still largely unknown. Using two-hybrid methodology we here demonstrate that the PDZ motif of neuronal nitric oxide synthase (nNOS) can mediate the binding to several other proteins in brain. Peptide library screening showed that proteins bearing a carboxy-terminal G(D,E)XV* sequence are pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 38 publications
2
54
0
1
Order By: Relevance
“…Therefore we wanted to determine whether there was a specific interaction between fulllength a 1A -ARs and nNOS in intact cells. These results support an interaction between nNOS and a 1A -ARs, which could be due to the previously reported interaction of the receptor C-terminus and the PDZ domain of nNOS [2]. However, this hypothesis is weakened by the unexpected observation that nNOS also co-immunoprecipitates with both a 1B and a 1D -ARs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore we wanted to determine whether there was a specific interaction between fulllength a 1A -ARs and nNOS in intact cells. These results support an interaction between nNOS and a 1A -ARs, which could be due to the previously reported interaction of the receptor C-terminus and the PDZ domain of nNOS [2]. However, this hypothesis is weakened by the unexpected observation that nNOS also co-immunoprecipitates with both a 1B and a 1D -ARs.…”
Section: Discussionsupporting
confidence: 88%
“…Previous work using a yeast two hybrid assay showed that the C-terminal 114 amino acids of rat a 1A -ARs (referred to by the previous name of a 1C -) strongly interacted with residues 1-111 of nNOS [2]. The bradykinin B2 receptor, also a G protein coupled receptor, has been shown to bind directly to the oxygenase domain of nNOS and form an inhibitory complex [8], and it has been proposed that nNOS is released and activated upon receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nNOS Binds CtBP at Its Peptide-binding Site-It has been shown previously that the PDZ domain of nNOS preferentially binds to peptides ending with the sequence G(D/E)AV (22,23) or EXAV (15,16). The last four amino acids of CtBP are SDQL, where the D fits the consensus for the second amino acid from the carboxyl terminus, and the L is a conservative substitution for the carboxyl-terminal V. To determine whether CtBP binds to the peptide-binding site in the PDZ domain of nNOS, we performed affinity chromatography of Cos-7 cells transfected with T7-tagged CtBP using a GST-nNOS-PDZ column.…”
Section: Isolation Of a 48-kda Protein That Binds To The Pdz Domain Omentioning
confidence: 99%
“…PDZ domains are globular structures that function as specific protein-recognition modules in a variety of cellular processes including the binding of carboxyterminus of E6 proteins (Harris and Lim, 2001;Thomas et al, 2001;Lee et al, 1997). In fact, a computer search program (http://scansite.mit.edu; Yaffe et al, 2001) identified the sequence, 35 GKGTSAADAVEVPAP 48 which immediately follows the L2G box in MGMT, as a class 3 PDZ site, originally identified in the neuronal nitric oxide synthase (nNOS) (Schepens et al, 1997). These structural considerations lend support to our observations that MGMT is a target for the E6/E6-AP system, however, the actual involvement of these motifs remains to be confirmed through mutation studies.…”
mentioning
confidence: 99%